PELESTARIAN RAWON NGULING SEBAGAI NILAI TAMBAH PADA PENGEMBANGAN WISATA KULINER TRADISIONAL INDONESIA - Sri Fajar Ayuningsih (Majalah Ilmiah Bijak, 2017)
Rawon is a typical food from East Java. Appearance of this meat soup is typical with blackish-colored sauce for wearing kebwak spice. Rawon Nguling's restaurant in Probolinggo is one of the most famous culinary destinations. This restaurant has been around since 1942 and now has 11 franchised restaurants in several cities in Indonesia. As one of the traditional culinary wealth, Rawon Nguling is worth preserving. For that required a proper development step by using the standard approach of spice Rawon Nguling and cooking techniques that is more practical ie freezing spices. From the result of research, Rawon Nguling standard spice (Rawon Nguling-Fajar seasoning) frozen up to 15 days in research scale, proved to be able to produce spice Rawon Nguling with flavor, smell / flavor, and color that is not different from Rawon Nguling fresh standard . In the form of frozen spices, the Rawon Nguling spices become more practical, more durable stored, and allow to be preserved. From the results of proximate analysis, Rawon Nguling is a food with a complete nutritional composition, especially as the fulfillment of animal protein requirements of 52.2% of AKG. In addition, spices in Ngurah Rawon cuisine also contain a variety of bioactive compounds that are good for maintaining health, including antioxidants, antimicrobial, antidiabetic, antitumor, and other functions.